ANALISIS INTERNAL MARKETING DALAM PENGEMBANGAN DAYA TARIK WISATA WENDIT WATER PARK - Sri Darmawati, Lusi Endang (Sekolah Tinggi Pariwisata AMPTA, 2018)
This study analyzes the influence of Internal Marketing (leadership, consultative, motivation, work standard, communication, and training) in developing the quality of Wendit Water Park attraction through description analysis. Respondents for this study were a total of 100 people who used for analysis.Respondents were taken randomly to answer the questionnaire. Testing was used for description analysis.The results of statistical analysis of description obtained that Internal Marketing has a strong contribution (80%) to the development of Wendit Water Park attraction, meaning that if Internal Marketing (leadership, consultative, motivation, work standards, communication, and training) is developed, it will lead to high quality tothe attraction of Wendit Water Park (WWP ). Six factors of Internal Marketing that reflect the success of marketing activities at Wendit Water Park (WWP) attraction.In average, WWP already has a good perception in scale 4 (70%), while the factor that has the highest frequency is sharing communication in Wendit Water Park (WWP). Keywords: Marketing; Tourist; Wendit Water Park